2021
DOI: 10.1177/00031348211023427
|View full text |Cite
|
Sign up to set email alerts
|

Combined Heart-Liver and Domino Liver Transplantation in Familial Amyloidosis

Abstract: Background Combined heart-liver transplantation (CHLT) is the only curative option for patients with concomitant pathology affecting the heart and liver. In some cases, the native livers of familial amyloidosis (FA) patients may be suitable for domino transplantation into other recipients. Methods Retrospective analysis (2013 to 2019) of all CHLT at our center was performed. Continuous data were presented as mean with standard deviation and discrete variables as percentages. Results Familial amyloidosis was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…35 Some studies have explored combined domino heart-liver transplantation for FAP with good outcomes. 36,37 However, give the small number of reports, we were not able to analyze and draw robust conclusions in the current study.…”
Section: Domino or Deceased Livers: Meta-analysismentioning
confidence: 70%
See 1 more Smart Citation
“…35 Some studies have explored combined domino heart-liver transplantation for FAP with good outcomes. 36,37 However, give the small number of reports, we were not able to analyze and draw robust conclusions in the current study.…”
Section: Domino or Deceased Livers: Meta-analysismentioning
confidence: 70%
“…The common right iliac vein was then anastomosed to the common stump of the domino graft middle and left hepatic vein; ultimately, the cadaveric IVC cuff was connected to the recipients middle and left hepatic veins 35 . Some studies have explored combined domino heart–liver transplantation for FAP with good outcomes 36,37 . However, give the small number of reports, we were not able to analyze and draw robust conclusions in the current study.…”
Section: Discussionmentioning
confidence: 82%
“…These explanted livers can then be transplanted into other end-stage liver patients with good results. While such domino liver transplantation was first described in 1995, a recent study reported the experience with domino liver transplant in CHLT [35,36]. This single-center experience appears promising with excellent survival rates.…”
Section: Combined Heart-liver Transplantationmentioning
confidence: 99%
“…Concerning the ATTR CA patients, the first proposed option was liver transplant (LT); subsequently, HTx has been combined with LT to avoid the potential development of the cardiomyopathy after LT alone [22][23] . Conversely, isolated HTx has been done in those patients without extracardiac deposits and end-stage HF, showing very encouraging results [24] .…”
Section: Introductionmentioning
confidence: 99%